Design and analysis for X band vsat application microstrip patch antenna at 7.5 ghz - Noralya Fatin Muzamil (Kulliyyah of Engineering, International Islamic University Malaysia, 2020)
In this research, a compact size and lightweight structure of rectangular microstrip patch antenna operating at 7.5 GHz is presented. This research is proposed to replace the existing parabolic reflector antenna for the VSAT application in terms of portability. The dimension of the proposed antenna is 19.00 mm × 30.55 mm which is compact in size. The simulation of microstrip patch antenna exhibits a good return loss, S11 of -42.09 dB, VSWR of 1.02 and gain of 7.18 dB by using CST Microwave Studio. The proposed antenna have been fabricated by using substrate RT/duroid ® High Frequency 5880 with dielectric of ( = . , tan () = . and t = 1.575mm). Then, the measurement return loss of the antenna prototype is performed using a Vector Network Analyzer, while the radiation patterns are measured in the anechoic chamber. The measurement of the antenna prototype exhibit a return loss, S11 of -30.53 dB, bandwidth of 455MHz, gain of 3.88 dB and efficiency of 68.71%.